Perancangan pet furniture dengan sistem knockdown untuk rumah tinggal - Soetedjo, Alyssa Lorenza; Kusumarini, Yusita; Lumintan, William Vijadhammo (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2024)
Having a pet is a hobby for some people to relieve stress or boredom, because their behavior is considered fun and attractive. Interaction between humans and pets occured in many areas in the house, caused positive psychological effects for their owners. However, the observation showed that not many owners pay attention to the facilities between humans and their pets. This caused a lack of place for interaction and a place to do activities in a relaxed and comfortable atmosphere. The design purpose is to help owners and pets do their activity together, and have a close relationship between each other. The design method is design thinking with the stages of understand, define, point of view, idea, prototype, test, and implement. The concept of this design is "merge", which means combining or joining. The final products are 3 sets of alternative designs and 1 set of realized pet furnituree, consist of storage cabinets, chairs, tables, and sidetable. The knockdown system is applied to this design so that the packaging and the product assembling is more practical and simpler. Activities they can do together, for example, when relaxing, watching TV, reading, or eating-drinking, they still can interact while using this product.